Interpretation in social life, social science, and marketing [ - O'Shaughnessy, John , 1927- (Routledge interpretive marketing research, 2009)
This book analyzes the nature and role of interpretation in social interactions, decision making in social science enquiries and consumer marketing, in the use of statistics and causal analysis, in consumer evaluations of products and in interpreting problematic situations along side biases arising from the emotions